Implementation Of Enterprise Resource Planning On Sales Management And Accounting & Finance Management Using Odoo Software (Case Study Of Furniture Company) - Ngurah Arya Bhaskara Wardhana; Gusti Agung Ayu Putri; Ni Kadek Dwi Rusjayanthi (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi), 2022)
Various benefits derived from the application of technology has caused company attempted to apply technology to their business processes, which can improve company performance. One of the most used technology that can utilized is ERP. ERP (Enterprise Resource Planning) is a software which can be used by companies to coordinate and integrate information in the company's business areas. Kenny Furniture is a company with the main activity of producing and selling furniture. The problem that faces by Kenny Furniture is the record of income and expenses of the Kenny Furniture is archived into the bookkeeping without using technology. The solution offered to overcome the problems of Kenny Furniture is implement ERP in the company's business processes, ERP implementation is carried out using the Odoo 15 application and only focuses on sales management and accounting and finance modules. Result of this research is the improvement of Kenny Furniture's Sales and financial recording business process.